ASTRA: Adaptive Student-Teacher Method for Robust Aggregation and Client Drift Reduction in Federated Learning - Gonçalves, João; Sousa, John; Veiga, Rafael; Bastos, Lucas; Pacheco, Lucas; Medeiros, Iago; Rosário, Denis; Cerqueira, Eduardo (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
Federated Learning (FL) faces critical convergence challenges when client data is heterogeneous (Non-IID). Existing solutions often trade computational efficiency for stability, incurring a high overhead. This paper proposes ASTRA (Adaptive Student-Teacher Method for Robust Aggregation and Client Drift Reduction in Federated Learning), a method that integrates geometric regularization with a dynamic self-distillation mechanism. Unlike static approaches, ASTRA employs a curriculum-based schedule that transitions from intensive guidance to periodic semantic correction. This strategy ensures that local updates remain aligned with the global objective (mitigating client drift), while drastically reducing the computational cost of the teacher model. Experimental results in Non-IID CIFAR-10 demonstrate that ASTRA outperforms the structural baseline (FedProx) by 32.7% in accuracy under severe heterogeneity, effectively preventing catastrophic divergence while maintaining training speeds within 2.3% of the lightweight FedAvg algorithm.